Semiconducting Studies of 8-Hydroxyquinoline-Biuret-Formaldehyde Terpolymer Resins - B. Gurnule, Wasudeo; Juneja, H.D.; Paliwal, L.J. (Asian Journal of Chemistry, 2010)
Terpolymer resins (8-HQBF) have been prepared by the condensation of 8-hydroxyquinoline and biuret with formaldehyde in the presence of acid catalyst and using varied molar ratios of reacting monomers. The electrical properties of 8-HQBF-1, 8-HQBF-2, 8- HQBF-3 and 8-HQBF-4 terpolymer resins have been Studied over a wide range of temperature (313 to 423 K). From the electrical conductivity of these terpolymer resins, activation energies of electrical conduction have been evaluated and values lie in the range 14.1 x 10-20 to 19 x 10-20 J/K. The plots of log σ vs. 103/T are found to be linear over a wide range of temperature, which indicate that the Wilson's exponential-law σ = σ0 exp (Ea/kT) is obeyed. On the basis of the above studies these terpolymers can be ranked as semiconductors.